Eugenia submontana (Myrteae, Myrtaceae), a new species from the Atlantic Forest of northeastern Brazil and notes on Eugenia culicina - Amorim, Bruno S.; Alves, Marccus (Phytotaxa, 2015)
A new species of Eugenia is here described and illustrated. Eugenia submontana is known from submontane Atlantic Forest in Pernambuco and is related to species bearing inflorescences with short internodes. E. submontana differs from related species in having sulcate midvein on adaxial leaf surface, short bracteoles and calyx lobes, a squared staminal ring and globose fruits with smooth surface. We also present here the first description of the fruits of Eugenia culicina, as well as a revision of its conservation status in light of new information.